Association between non‐invasively diagnosed hepatic steatosis and chronic kidney disease in Chinese adults on their health check‐up. Issue 4 (April 2017) - Zeng, Jing; Sun, Chao; Sun, Wan Lu; Chen, Guang Yu; Pan, Qin; Yan, Shi Yan; Xu, Zheng Jie; Chen, Yuan Wen; Fan, Jian Gao
Abstract : OBJECTIVE: To explore the association between chronic kidney disease (CKD), graded by the estimated glomerular filtration rate (eGFR), and non‐alcoholic fatty liver disease (NAFLD) using controlled attenuation parameter (CAP) and fatty liver index (FLI) values in Chinese adults undergoing routine health examinations. METHODS: A total of 731 adult participants without diabetes mellitus or significant alcohol consumption who underwent routine health examinations were included. Their eGFR, CAP, FLI and abdominal ultrasonography results were assessed. RESULTS: The prevalence of ultrasound‐diagnosed NAFLD and CKD (eGFR <60 mL/min per 1.73 m 2 ) was 36.1% and 6.6%, respectively. CKD was more common in NAFLD patients than in those without (10.6% vs 4.3%, P  < 0.001). The CAP and FLI values were significantly higher in the NAFLD group than in those without, but the change in the eGFR was negligible between the two groups. eGFR was negatively correlated with CAP ( r  = −0.189, P  = 0.003) and FLI values ( r  = −0.130, P  = 0.045). Moreover, eGFR was significantly lower in participants with CAP >292 dBm or FLI ≥60 than in those with CAP <238 dBm or FLI <30, respectively (both P  < 0.05). The CAP value (odds ratio [OR] 1.099, 95% confidence interval [CI] 1.091–1.108, P  = 0.021) was an independent risk factor for CKD. CONCLUSIONS: A diagnosis of hepatic steatosis is related to an increased risk of CKD among non‐alcoholic and non‐diabetic Chinese adults regardless of whether the diagnosis was acquired via ultrasound, CAP or FLI. Increased hepatic lipid content may contribute to CKD development.